Penerapan Kimia Hijau Dan Pengetahuan Lingkungan Serta Keterkaitannya Dengan Perilaku Peduli Lingkungan - Santosa, Ni Ketut Yuli; Sulistyowati, Lilik; Aji, Sandra Sukmaning (Universitas Tanjungpura, 2024)
The application of green chemistry and environmental knowledge plays an important role in shaping individuals' awareness and actions toward environmental sustainability. By applying green chemistry and having good environmental knowledge, it can increase environmental awareness, so that it can increase environmental care behavior. Students who have good environmental knowledge have a more positive attitude toward the environment and tend to care more about the environment. Based on the background, the objectives of this research are: (1) to analyze the school community's perception of the concept of green chemistry and (2) to analyze the correlation between understanding green chemistry and the environment together with environmental care behavior. The research was conducted at SMA Kristen Harapan Denpasar using a random sampling technique with a sample size of 150 people. This research